Annual feeding rate of the millipede Glomeris marginata on holm oak ( Quercus ilex) leaf litter under Mediterranean conditions - DAVID, J. F.; Gillon, Dominique (Pedobiologia, 2002)
The annual consumption and assimilation rates of Quercus ilex leaf litter by the millipede Glomeris marginata were estimated under Mediterranean conditions simulated in the laboratory. Measurements were made on six occasions throughout the year to take into account seasonal variations in (i) the quality of decomposing leaves, (ii) the physiological state of the animals, and (iii) temperature plus photoperiod. The mean weight-specific consumption rate was 14 g (dry weight) g-1 (live weight) y-1 , which is much higher than published figures for Mediterranean oak leaf litter. The consumption rate was highest in spring (51 mg g-1 d-1 ) and lowest in summer (28 mg g-1 d-1 ), the summer consumption rate being even lower when determined with air-dried leaves (17 mg g-1 d-1 ). Assimilation efficiency averaged 6 % for the year, with a maximum in spring (9 %) and a minimum in winter (1 %). A much higher assimilation efficiency (29 %) was measured with freshly fallen leaves, but a food preference experiment showed that these leaves were generally avoided and that G. marginata preferred more decomposed leaves despite their lower digestibility. It is concluded that these saprophagous macroarthropods – with field biomasses of 7–11 g (live weight) m-2 – produce considerable amounts of faecal pellets in Mediterranean oak forests.
Keywords: assimilation efficiency; diplopoda; feeding rate; Mediterranean forests; soil macrofauna

Annual feeding rate of the millipede Glomeris marginata on holm oak ( Quercus ilex) leaf litter under Mediterranean conditions (Pedobiologia, 2002)
The annual consumption and assimilation rates of Quercus ilex leaf litter by the millipede Glomeris marginata were estimated under Mediterranean conditions simulated in the laboratory. Measurements were made on six occasions throughout the year to take into account seasonal variations in (i) the quality of decomposing leaves, (ii) the physiological state of the animals, and (iii) temperature plus photoperiod. The mean weight-specific consumption rate was 14 g (dry weight) g-1 (live weight) y-1 , which is much higher than published figures for Mediterranean oak leaf litter. The consumption rate was highest in spring (51 mg g-1 d-1 ) and lowest in summer (28 mg g-1 d-1 ), the summer consumption rate being even lower when determined with air-dried leaves (17 mg g-1 d-1 ). Assimilation efficiency averaged 6 % for the year, with a maximum in spring (9 %) and a minimum in winter (1 %). A much higher assimilation efficiency (29 %) was measured with freshly fallen leaves, but a food preference experiment showed that these leaves were generally avoided and that G. marginata preferred more decomposed leaves despite their lower digestibility. It is concluded that these saprophagous macroarthropods – with field biomasses of 7–11 g (live weight) m-2 – produce considerable amounts of faecal pellets in Mediterranean oak forests.

Internal remobilization of carbohydrates, lipids, nitrogen and phosphorus in the Mediterranean evergreen oak Quercus ilex (Tree Physiology, 2001)
Remobilization of internal resources is an important mechanism enabling plants to be partly independent of external nutrient availability. We assessed resource remobilization during the growing period in woody and foliar tissues of leafy branches of mature evergreen Mediterranean oak (Quercus ilex L.) at three field sites. We compared nonstructural carbohydrates, lipids, nitrogen and phosphorus pools in leaves and stems before bud burst (March) and at the end of the growing period (July). We also experimentally defoliated leafy branches to determine the storage function of old leaves. Changes in pools of carbon compounds in leaves and stems during spring and in response to defoliation indicated that foliar and woody tissues could provide carbon to support shoot growth. Independently of stem age, soluble sugar and lipid pools decreased significantly during spring. Changes in leaf pools between March and July involved all compounds measured except starch and were accompanied by a 5%; decrease in mean leaf biomass. During the same period, 15%; of the nitrogen and 25%; of the phosphorus were removed from leaves. In contrast, woody tissues did not remobilize nitrogen or phosphorus. Our results support earlier hypotheses that leaves of evergreen species have a primary role in resource remobilization.
10.1093/treephys/21.1.9

Internal remobilization of carbohydrates, lipids, nitrogen and phosphorus in the Mediterranean evergreen oak Quercus ilex - Cherbuy, Bénédicte; Joffre, Richard; Gillon, Dominique; Rambal, Serge (Tree Physiology, 2001)
Remobilization of internal resources is an important mechanism enabling plants to be partly independent of external nutrient availability. We assessed resource remobilization during the growing period in woody and foliar tissues of leafy branches of mature evergreen Mediterranean oak (Quercus ilex L.) at three field sites. We compared nonstructural carbohydrates, lipids, nitrogen and phosphorus pools in leaves and stems before bud burst (March) and at the end of the growing period (July). We also experimentally defoliated leafy branches to determine the storage function of old leaves. Changes in pools of carbon compounds in leaves and stems during spring and in response to defoliation indicated that foliar and woody tissues could provide carbon to support shoot growth. Independently of stem age, soluble sugar and lipid pools decreased significantly during spring. Changes in leaf pools between March and July involved all compounds measured except starch and were accompanied by a 5%; decrease in mean leaf biomass. During the same period, 15%; of the nitrogen and 25%; of the phosphorus were removed from leaves. In contrast, woody tissues did not remobilize nitrogen or phosphorus. Our results support earlier hypotheses that leaves of evergreen species have a primary role in resource remobilization.
10.1093/treephys/21.1.910.1093/treephys/21.1.9
Keywords: defoliation; Growth; nutrient storage; resource remobilization

Changes in litter during the initial leaching phase: an experiment on the leaf litter of Mediterranean species (Soil biology and biochemistry, 1995)
A laboratory experiment was carried out with the litter of 7 Mediterranean species of plants to compare their mass losses during the initial leaching phase of decomposition. To this end, the leaf and needle litter of deciduous, marcescent (deciduous species in which the withered leaves remain on the tree. for several months) and evergreen broad-leaved species and pine was immersed for 10 days in demineralized water, in the dark at 22°C. Samples were taken at 1,6, 24,72, 168 and 240 h. Depending on the species, the litter lost between ‘T-15% of initial dry mass, and water content values were between 130-360% of dry mass. The water absorption rate was positively correlated with the initial cellulose content of the litter and negatively correlated wil:h the initial leaf density, but the water content at the end of the experiment, the leaching rate and the total mass loss were uncorrelated with any of the initial litter characteristics studied. For 100 g of litter at the start (as dry matter), the losses after 240 h of immersion in water were, when they were significant, 5-8 g of C, 70-l 30 mg of N (significant for 3 species), 4-40 mg of soluble sugars and 3 g of inorganic elements (significant for only 2 species). In contrast, the quantities of lignin and cellulose in the litter remained unchanged. Most of the leaching losses (SCrSO%) therefore consisted of C. During leaching, the litter showed a tendency to become more concentrated in cellulose and lignin and poorer in sugars. Pine needle litter was distinguished by its low water absorption and low mass loss during leaching. In general, the litters of deciduous species were more absorbent than the litters of evergreen species. In contrast, the losses of water-soluble substances were not significantly different between these 2 groups of litters. In the broad-leaved species, the losses of water-soluble substances were slower and 2-3 times lower, compared to results already published for species from mesic biomes